Seeking and receiving hypertension and diabetes mellitus care in Tanzania. - Kassimu Tani; Brianna Osetinsky; Grace Mhalu; Sally Mtenga; Günther Fink; Fabrizio Tediosi (PLoS ONE)
The rapid increase in chronic non-communicable diseases (NCDs) poses a major challenge to already strained health systems in sub-Saharan Africa. This study investigates the factors associated with seeking and receiving NCD services in Tanzania, using a household survey and client exit interview data from Kilombero and Same districts. Both districts are predominantly rural, with one semi-urban area called Ifakara town and Same town. Of the 784 household survey respondents, 317 (40.4%), 37 (4.7%), and 20 (2.5%) were diagnosed with hypertension, diabetes mellitus, and other NCDs, respectively, of whom 69% had sought care in the past six months. After controlling for covariates, those enrolled in the National Health Insurance Fund (NHIF) and those who received a user fees waiver were more likely to use health services. However, even when NCD patients managed to access the care they needed, they were likely to receive incomplete services. The main reason for not receiving all services at the health facility visited on the day of the survey was drug stock-outs. Among health care users, those registered with the improved Community Health Funds (iCHF) were less likely to receive all prescribed services at the health facility visited than uninsured patients. The findings of this study highlight the need to strengthen both primary care and social health protection systems to improve access to needed care for NCD patients.